The Historical Role of the International Labour Organization for the Establishment of International Standards for Labour and Social Human Rights - Staykov, Ivaylo (Yearbook of the Law Department, 2019)
The subject of the research is the role of the International Labour Organization in establishing international standards for labour and social human rights. The analysis is dedicated to the 100th anniversary of the creation of this universal specialized international organization.